THE THREAT OF VALUABLE TERRAINS OF NATURE ON EXAMPLE OF ZAKOPANE (POLAND) - BIEDRAWA, Agnieszka; SOBCZYK, Wiktoria (Trends in education, 2008)
The scenery is the synthesis of natural environment, cultural as well as visual and every of these features requires the separate approach in formation and the protection. Zakopane is a city situated at foot of Tatras, on height 830 m n.p.m. The neighborhoods of city are dreamt place of admiring the natural values and the mountain tourism. The subject of this article is a short profile of legal forms of protecting the environment and landscape. The aim of this publication is indication the threats of growing mass tourism and inappropriate economy wastes.
Keywords: tereny przyrodniczo cenne; zagrozenia srodowiska przyrodniczego